In Vitro and In Vivo Evaluation of Silver Nanoparticles Phytosynthesized Using Raphanus sativus L. Waste Extracts - Ungureanu, Camelia (Materials (Basel), 2021)
The aim of the current paper is the development of phytosynthesized silver nanoparticles mediated by Raphanus sativus L. extracts obtained through two extraction methods (temperature and microwave) and to test their potential application for controlling apple crops pathogens. The phytosynthesized materials were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. All the materials were evaluated in terms of antioxidant and in vitro antimicrobial activity (against bacteria, molds, and yeast: Escherichia coli ATCC 8738, Staphylococcus aureus ATTC 25923, Pseudomonas aeruginosa ATCC 9027, Salmonella typhimurium ATCC 14028, Candida albicans ATCC 10231, Venturia inaequalis, Podosphaera leucotricha, Fusarium oxysporum ATCC 48112, Penicillium hirsutum ATCC 52323, and Aspergillus niger ATCC 15475). Considering the results obtained in the in vitro assays, formulations based on nanoparticles phytosynthesized using Raphanus sativus L. waste extracts (RS1N) were evaluated as potential antifungal agents for horticultural crops protection, against Venturia inaequalis and Podosphaera leucotricha through in vivo assays. For the DPPH assay, the inhibition (%) varied between 37.06% (for RS1N at 0.8 mg/mL concentration) and 83.72% (for RS1N at 7.2 mg/mL concentration) compared to 19.97% (for RS2N at 0.8 mg/mL) and only 28.91% (for RS2N at 7.2 mg/mL). Similar results were obtained for RS3N (85.42% inhibition at 7.2 mg/mL) compared with RS4N (21.76% inhibition at 7.2 mg/mL). Regarding the ABTS assay, the highest scavenger activity values were recorded for samples RS1N (91.43% at 1.6 mg/mL) and RS3N (96.62% at 1.6 mg/mL).